DamX Controls Reversible Cell Morphology Switching in Uropathogenic Escherichia coli - Surabhi Khandige (American Society for Microbiology, 2016)
ABSTRACT The ability to change cell morphology is an advantageous characteristic adopted by multiple pathogenic bacteria in order to evade host immune detection and assault during infection. Uropathogenic Escherichia coli (UPEC) exhibits such cellular dynamics and has been shown to transition through a series of distinct morphological phenotypes during a urinary tract infection. Here, we report the first systematic spatio-temporal gene expression analysis of the UPEC transition through these phenotypes by using a flow chamber-based in vitro infection model that simulates conditions in the bladder. This analysis revealed a novel association between the cell division gene damX and reversible UPEC filamentation. We demonstrate a lack of reversible bacterial filamentation in a damX deletion mutant in vitro and absence of a filamentous response by this mutant in a murine model of cystitis. While deletion of damX abrogated UPEC filamentation and secondary surface colonization in tissue culture and in mouse infections, transient overexpression of damX resulted in reversible UPEC filamentation. In this study, we identify a hitherto-unknown damX-mediated mechanism underlying UPEC morphotypical switching. Murine infection studies showed that DamX is essential for establishment of a robust urinary tract infection, thus emphasizing its role as a mediator of virulence. Our study demonstrates the value of an in vitro methodology, in which uroepithelium infection is closely simulated, when undertaking targeted investigations that are challenging to perform in animal infection models. IMPORTANCE Urinary tract infections (UTIs) are most often caused by uropathogenic Escherichia coli (UPEC) and account for a considerable health care burden. UPEC exhibits a dynamic lifestyle in the course of infection, in which the bacterium transiently adopts alternative morphologies ranging from rod shaped to coccoid and filamentous, rendering it better at immune evasion and host epithelium adhesion. This penchant for morphotype switching might in large measure account for UPEC’s success as a pathogen. In aiming to uncover genes underlying the phenomenon of UPEC morphotype switching, this study identifies damX, a cell division gene, as a mediator of reversible filamentation during UTI. DamX-mediated filamentation represents an additional pathway for bacterial cell shape control, an alternative to SulA-mediated FtsZ sequestration during E. coli uropathogenesis, and hence represents a potential target for combating UTI.